Progesterone in women with arrested premature labor, a report of a randomised clinical trial and updated meta-analysis - Stephen Wood; Yacov Rabi; Selphee Tang; Rollin Brant; Susan Ross (BMC, 2017)
Abstract Background Progesterone may be effective in prevention of premature birth in some high risk populations. Women with arrested premature labor are at risk of recurrent labor and maintenance therapy with standard tocolytics has not been successful. Methods Randomized double blinded clinical trial of daily treatment with 200 mg vaginal progesterone in women with arrested premature labor and an updated meta-analysis. Results The clinical trial was terminated early after 41 women were enrolled. Vaginal progesterone treatment did not change the median gestational age at delivery: 36+2 weeks versus 36+4 weeks, p = .865 nor increase the mean latency to delivery: 44.5 days versus 46.6 days, p = .841. In the updated meta-analysis, progesterone treatment did reduce delivery <37 weeks gestation and increase latency to delivery, but this treatment effect was not evident in the high quality trials: (OR 1.23, 95% CI 0.91, 1.67) and (−0.95 days, 95% CI −5.54, 3.64) respectively. Conclusion Progesterone is not effective for preventing preterm birth following arrested preterm labor.